ORBIS project – where have we arrived? - Skotnicki, Marcin; Jakubowska, Emilia; Smułek, Wojciech; Davin, Sharon; Tajber, Lidia; Lulek, Janina (Journal of Medical Science, 2023)
The Open Research Biopharmaceutical Internships Support project (ORBIS) was a response to the scientific, economic, and social challenge of increasing the effectiveness and productivity of the drug development process, both for innovative and (super)generic drugs. The overarching objective of the ORBIS project was to form a transnational and intersectoral cooperation network of academic and industrial organisations delivering a joint research programme. The research aimed at improving the preclinical pathway of drug development and manufacturing, focusing on technological and methodological improvements of the existing processes. The participating staff from all institutions have developed new skills, were exposed to new work and research environments, and have significantly broadened their career perspectives. More than 450 months of secondments were completed, and over 175 early-stage and experienced researchers participated in the exchange. This review aims to present some aspects of the scientific, training, and organisational activities of the consortium, bringing together representatives of both the academic sector as well as small and medium-sized pharmaceutical enterprises.